Semiempirical method for process analysis on electric arc spray forming of Fe-0.06%C steel rings - Seok, H; Llewellyn, H; Lee, J; Grant, P (2002)
A numerical program, which calculates the temperature profiles of electric arc spray formed (EASF) preforms, is coded on the basis of a shape forming model, droplet flight dynamics, and the boundary fitted coordinate (BFC) method for the calculation of heat transfer equations. Some thermophysical input data for the calculations, such as average droplet temperature impinging on the deposit surface, effective thermal conductivity of the deposit, and heat transfer coefficient at the interface and surface, are given by matching the experimental results with the numerical calculation results. Using the program, the temperature changes of the Fe-0.06%C steel ring deposit during the EASF process are calculated. The effects of the EASF parameters, such as substrate rotation velocity, average droplet temperature, and wire feedrate, on the temperature changes of the Fe-0.06%C steel ring preforms are also estimated.